2015
DOI: 10.5057/ijae.ijae-d-14-32
|View full text |Cite
|
Sign up to set email alerts
|

Analyses of Local Mascot Characters and Proposal of Automatic Character Creation System Using Affective Words

Abstract: In this paper, first, analyses of local community mascot characters are carried out to obtain knowledge to be the popular ones. Next a mascot characters automatic creation system is proposed using these findings. As for the analyses, we used 200 mascot characters. Many interesting findings could be obtained such that dark-round eyes tend to contribute to be popular as a mascot character. The proposed system utilizing these findings can create a mascot character reflecting a user's image inputted by affective w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 8 publications
(6 reference statements)
0
1
0
1
Order By: Relevance
“…On the other hand, unusual combinations, such as mixing a cow and a bird, while eye-catching, may be deemed unfamiliar and less friendly (Jiyavorananda et al, 2016). In terms of form, a study by Fathoni (2023) showed that circular body shapes are preferred, while another analysis by Hotogi and Hagiwara (2015) showed shorter legs tend to be favored. In terms of features, the aforementioned study by Hotogi and Hagiwara (2015) showed that circular black eyes are preferred, whil another analysis by Ito and Yamashita (2014) showed that rounded noses and animal-like mouths contribute positively in terms of viewer preference and cuteness and are indicated to create a good impression.…”
Section: Mascot Character Designmentioning
confidence: 99%
See 2 more Smart Citations
“…On the other hand, unusual combinations, such as mixing a cow and a bird, while eye-catching, may be deemed unfamiliar and less friendly (Jiyavorananda et al, 2016). In terms of form, a study by Fathoni (2023) showed that circular body shapes are preferred, while another analysis by Hotogi and Hagiwara (2015) showed shorter legs tend to be favored. In terms of features, the aforementioned study by Hotogi and Hagiwara (2015) showed that circular black eyes are preferred, whil another analysis by Ito and Yamashita (2014) showed that rounded noses and animal-like mouths contribute positively in terms of viewer preference and cuteness and are indicated to create a good impression.…”
Section: Mascot Character Designmentioning
confidence: 99%
“…Colours play a pivotal role in shaping a character's impression (Hotogi & Hagiwara, 2015). For mascots, it's crucial to align colour choices with the brand's existing palette for consistency (Henderson, 2021).…”
Section: Colour Palettementioning
confidence: 99%
See 1 more Smart Citation
“…They functioned as a communicator to the audience by focusing on positive emotions with their cuteness -cute visual appearance widely used in local mascot designs in Japan. Analysis of local mascot design in Japan raises ICADECS several affective words such as cheerful, simple, amiable, humorous, gentle, innocent, cute, gorgeous, carefree [3]. Another opinion states that the cute nature reflected in the emotions of social relationships such as moved, touched, heartwarming, nostalgia, patriotism, team spirit, and feeling God's love [4].…”
Section: Introductionmentioning
confidence: 99%
“…Berbagai maskot diciptakan untuk membantu proses komunikasi kepada khalayak sasaran, tujuannya untuk menggerakkan emosi positif dengan penampilan visual. Menurut Hotogi (Hotogi & Hagiwara, 2015) ada beberapa kata afektif yang didapat dari analisis desain karakter maskot lokal yang ada di jepang, seperti: cheerful, simple, amiable, humorous, gentle, innocent, cute, gorgeous, carefree. Kata-kata ini yang nantinya dapat diterjemahkan dengan menggunakan bahasa visual, dengan demikian karakter akan memiliki tampilan yang afektif dan menarik.…”
unclassified